Female Learner Experiences in Accessing University Education in Kenya through Distance Mode: Addressing Constraints, Prospects and Policy Directions (Global Journal of Human-Social Science, 2015)
This study assessed challenges experienced by 1,400 women distance learners in Kenyan public and private universities. A cross-sectional survey design with quantitative and qualitative approaches guided the research process. Quantitative analysis yielded descriptive statistics and severity scores; while qualitative data were transcribed, clustered into nodes and explored for emerging themes. The results showed that about 77% of the participants believed that irregular and unsystematic supply of course materials disrupted learning continuity and was considered the most severe challenge experienced by learners. Whereas, 66.9% identified the turnaround time for assignments as a problem affecting study plans, 60.7% noted that compulsory submission of assignments was a key challenge. The study recommends the need for institutions to: establish a supervisory system, linking learners with administration to ensure a consistent supply of reading materials; computerize student information system to improve administrative effectiveness; develop a master plan for tutorials; and standardize the turn-around time for assignments.